The effect of country of origin image, ethnocentrism, and religiosity on purchase intentions: an empirical investigation on Bangladeshi consumers - Haque, A. K. M. Ahasanul; Anwar , Naila; Sarwar , Abdullah (Associated Management Consultants (P) Ltd ., 2015)
This research endeavour was undertaken in order to understand the effect of three different aspects namely, Country of Origin, Ethnocentrism, and Religiosity on Bangladeshi consumers' intention of purchasing imported or foreign products. At the initial stage of the study, 260 questionnaires were given out to Bangladeshi consumers in the cities of Dhaka and Chittagong. However, out of the 260 questionnaires, 230 were validated and tested for the purpose of statistical analysis. Descriptive analysis was conducted first in order to assess the demographic characteristics of the respondents, after which, exploratory factor analysis (EFA) was conducted, and finally, the hypotheses were tested, and the proposed model was verified through the application of structural equation modelling (SEM). The findings demonstrated that Country of Origin Image, Ethnocentrism, and Religiosity significantly affected Bangladeshi consumers' intention of buying imported products. The findings generated from this study will provide useful information to marketers who are selling imported or foreign products in the Bangladeshi market as well as help them in developing effective marketing strategies. At the same time, this study is also a meaningful contribution to literature, given the scarcity of research studies on this topic pertaining to Bangladesh.